The Effect of Size, Profitability, Leverage and Capital Intensity on the Effective Tax Rate (ETR) in Food and Beverage Industry Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX) - Satyo, Yuwono Aji; Paranita, Ekayana Sangkasari (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze the effect of Company Size, Profitability, Leverage, and Capital Intensity on Effective Tax Rate (ETR) in food and beverage industry sub- sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2023. The approach used is quantitative with an associative approach, which allows empirical identification of the relationship between independent and dependent variables. The sample was determined using purposive sampling method, which resulted in 31 companies in the food and beverage industry sector with a total of 124 observations. Data analysis was performed using panel data regression using Eviews software version 12. The results showed that company size and leverage had no significant effect on ETR. Meanwhile, profitability and capital intensity have a significant positive effect on ETR. Simultaneously, the four independent variables proved to have a significant effect on ETR. These findings provide important implications for company management and policy makers to consider internal factors in the formulation of a tax strategy that is balanced between fiscal efficiency and regulatory compliance.